2006
DOI: 10.1523/jneurosci.3253-06.2006
|View full text |Cite
|
Sign up to set email alerts
|

Nursing-Induced Somatosensory Cortex Plasticity: Temporally Decoupled Changes in Neuronal Receptive Field Properties Are Accompanied by Modifications in Activity-Dependent Protein Expression

Abstract: This study is an attempt to gain insight into the malleability of representational maps in the primary somatosensory cortex in relation to the expression of proteins involved in inhibitory and excitatory neurotransmitter systems that contribute to maintain these maps in a dynamic state. Malleability of somatosensory maps is characterized by changes in the sizes of neuron receptive fields (RFs) affecting the representational grain and in the locations and submodalities of these RFs modifying the map extent. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
43
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(45 citation statements)
references
References 63 publications
2
43
0
Order By: Relevance
“…The cutaneous RF enlargement found in HG rats is consistent with the decrease in GABA immunoreactivity recorded in the limb representation of the rats S1 cortex after 14 days of exposure to HG (D'Amelio et al 1998). Furthermore, an expansion of cutaneous RFs in the S1 cortex was found when GABA-mediated local inhibition was antagonized (Alloway et al 1989 regation of inputs converging onto neuronal targets was reshaped on a timescale closely dependent on behaviorally driven changes in somatosensory inputs (Rosselet et al 2006). The reversibility vs. retention of different neuronal response properties, after the animals were exposed to NG, shows that the use-dependent synaptic mechanisms leading to masking/ unmasking of less/more effective inputs or to synaptogenesis at maturity are expressed within limits of representational malleability stabilized by somatosensory experience during a critical developmental period.…”
Section: Summary Of Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…The cutaneous RF enlargement found in HG rats is consistent with the decrease in GABA immunoreactivity recorded in the limb representation of the rats S1 cortex after 14 days of exposure to HG (D'Amelio et al 1998). Furthermore, an expansion of cutaneous RFs in the S1 cortex was found when GABA-mediated local inhibition was antagonized (Alloway et al 1989 regation of inputs converging onto neuronal targets was reshaped on a timescale closely dependent on behaviorally driven changes in somatosensory inputs (Rosselet et al 2006). The reversibility vs. retention of different neuronal response properties, after the animals were exposed to NG, shows that the use-dependent synaptic mechanisms leading to masking/ unmasking of less/more effective inputs or to synaptogenesis at maturity are expressed within limits of representational malleability stabilized by somatosensory experience during a critical developmental period.…”
Section: Summary Of Resultssupporting
confidence: 80%
“…The enduring effects of early HG rearing are at variance with the reversibility of alteration found in adult somatosensory maps following various manipulations (see for reviews Barnes and Finnerty 2010;Buonomano and Merzenich 1998;Xerri 2008), such as experimental syndactyly (Clark et al 1988), limb immobilization (Coq and Xerri 1999), or natural episodic behavior (nursing; Rosselet et al 2006). These HG-induced sustained alterations provide an additional argument in favor of a critical period in the maturation of somatosensory maps, previously shown for the development of the whisker-barrel system (see Erzurumlu and Gaspar 2012 for review).…”
mentioning
confidence: 99%
“…Experimental work on a timescale of days to weeks reveals that cortical map expansion and RF sharpening/contraction induced by the repetitive cutaneous stimulation during nursing is associated with changes in the inhibitory and excitatory system (Rosselet et al, 2006). The authors show that, at different time points, only one of the systems is changed.…”
Section: Introductionmentioning
confidence: 96%
“…Based on theoretical and experimental work, it has been suggested that the maintenance of cortical maps and RFs arises from a meticulous balance of both local and global mechanisms based on feedforward and recurrent inputs (Stratford et al, 1996;Miller et al, 2001;Kalarickal and Marshall, 2002), on alterations of both excitatory and inhibitory mechanisms (Heizmann, 1993;Jones, 2000;Kalarickal and Marshall, 2002;Rosselet et al, 2006), and on a continues protein synthesis (Kleim et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Western blot analysis was performed as described in Rosselet et al (2006). In brief, tissue samples were homogenized and denatured in Tris-Cl buffer.…”
Section: Semi-quantitative Western Blottingmentioning
confidence: 99%